Reindeer Husbandry - Adaptation to the Changing Arctic, Volume 1 - Mathiesen, Svein D.; Eira, Inger Marie G.; Turi, Ellen Inga; Oskal, Anders; Mikhail, Pogodaev; Marina, Tonkopeeva (Springer, 2022)
Reindeer Husbandry: Adaptation to the Changing Arctic, Volume 1 is the first of two books published by Springer Nature. This first book consists of ten peer-reviewed chapters with each chapter reviewed by two to six renowned international researchers and scientists. The authors express their immense gratitude to the reviewers and deeply acknowledge their unique contribution. This book addresses the critical issue faced by Indigenous peoples in the Arctic: climate change, the ways in which it affects their societies and livelihoods, environment, and economies. It is important that all available forms of knowledge – academic, traditional, Indigenous, and local – are included when addressing the adaptation and resilience of reindeer husbandry in the Circumpolar North. The two volumes provide novel insights into the Arctic Indigenous reindeer herding communities and how resilience can be built locally through the use of traditional knowledge and co-production.